A Study on the Feasibility of Retrofitting Tunku Tun Aminah Library Towards Green Building - ANUAR, NURUL FATIN NABILAH; JAILANI, JUNAIDAH (Recent Trends in Civil Engineering and Built Environment, 2023)
Green buildings are designed to enhance energy efficiency and resource management. Whereas, retrofit is the method of transforming and modifying systems and technologies in an existing building to combat environmental depreciation. Hence, retrofitting existing buildings that meet green building requirements enhances the sustainable environment. In Malaysia, the increment of energy consumption in institutional buildings is attributable to the university’s activities and population. Therefore, the purpose of this study is to analyze whether the exiting UTHM’s library building applied with the concept of green building and explore the feasibility of retrofitting UTHM building that responds to sustainable green building standards. The approach for this study was developed through a literature review and quantitative research using a questionnaire survey as a method. The data gathered was then evaluated utilising SPSS to obtain the average index.  The results show that the UTHM’s library building has fulfilled only two of the GBI criteria which are Energy Efficiency and Indoor Environmental Quality. Thus, all sub-elements with an average index lower than 3.5 should be considered as potential retrofitting in the future. To conclude, the campus management could consider immediate measure to comply with green building standards to optimize energy consumption, which can be accomplished through appropriate retrofitting of existing structures.